PERAN PEJABAT PEMBUAT AKTA TANAH DALAM PENDAFTARAN HAK ATAS TANAH - Purnama, Novita Cahaya; Ummah, Arsal (UNES Journal of Swara Justisia, 2017)
Land is very important for human life. Given the importance of the function of land for human life, then to provide legal certainty for the holder of the right to land, the land needs to be registered. The official authorized to register the land is the PPAT which has a very important role in maintaining the land registration data, ie making evidence about the occurrence of legal acts concerning a particular plot of land which then becomes the basis for registering the change of juridical data caused by the legal act. PPAT also assists the head of the land office as the executor of land registration, by providing evidence that will be the basis for registration of changes in land registration data. In addition, PPAT has the main duty to carry out part of land registration activities by making deed as evidence of certain legal acts. This research is empirical research with primary data as main data collected through interview technique, and also supported secondary data collected through literature study / document.